DYNAMIC LOADING DRIVES AUXILIARY UNITS OF LOCOMOTIVES - Surovtsev, P. M.; Sokolov, Yu. M. (Science and Transport Progress, 2004)
Considered questions: increase of reliability of subsidiary drivers of main-line and shunting diesel and electric locomotives and engineering solutions implemented during their retrofit.